Comparative genomics of Roseobacter clade bacteria isolated from the accessory nidamental gland of Euprymna scolopes - Collins, Andrew J.; Fullmer, Matthew S.; Gogarten, Johann P.; Nyholm, Spencer V. (Frontiers in Microbiology, 2015)
The accessory nidamental gland (ANG) of the female Hawaiian bobtail squid, Euprymna scolopes, houses a consortium of bacteria including members of the Flavobacteriales, Rhizobiales and Verrucomicrobia but is dominated by members of the Roseobacter clade (Rhodobacterales) within the Alphaproteobacteria. These bacteria are deposited into the jelly coat of the squid's eggs, however the function of the ANG and its bacterial symbionts has yet to be elucidated. In order to gain insight into this consortium and its potential role in host reproduction, we cultured 12 Rhodobacterales isolates from ANGs of sexually mature female squid and sequenced their genomes with Illumina sequencing technology For taxonomic analyses, the ribosomal proteins of 78 genomes representing both roseobacters and non-roseobacters along with a separate MLSA analysis of 33 housekeeping genes from roseobacter organisms placed all 12 isolates from the ANG within two groups of a single Roseobacter clade. Average nucelotide identity analysis suggests the ANG isolates represent 3 genera (Leisingera, Ruegeria and Tateyamaria) comprised of 7 putative species groups. All but one of the isolates contains a predicted Type VI secretion system, which has been shown to be important in secreting signaling and/or effector molecules in host-microbe associations and in bacteria-bacteria interactions. All sequenced genomes also show potential for secondary metabolite production, having predicted to be involved with the production of acyl homoserine lactones (AHLs) and/or siderophores. An AHL bioassay confirmed AHL production in three tested isolates and from whole ANG homogenates. The dominant symbiont, Leisingera sp. ANG1, showed greater viability in iron-limiting conditions compared to other roseobacters, possibly due to higher levels of siderophore production. Future comparisons will try to elucidate novel metabolic pathways of the ANG symbionts to understand their putative role in host development.